The Effect of Profitability, Liquidity and Asset Structure on Debt Policy - Hidayat, Muhamad Lukman; Cahya, Indra; Anwar, Saeful (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The purpose of this study is to examine the effect of Profitability, as measured by Return on Asset (ROA), the effect of Liquidity as measured by Current Ratio (CR) and Asset Structure, as measured by (SA) on debt policy as measured by Debt-to-Equity Ratio (DER) in Basic Material Sub-Sector companies listed on the IDX for the period 2019-2023 (Case Study on 28 Basic Material Companies on the Indonesia Stock Exchange). The technique used in this study uses purposive sampling technique. The data analysis method used is multiple regression with Stata14 software. The results of the study show that simultaneously there is an influence of the independent variables Profitability (ROA), Liquidity (CR), and Asset Structure (SA) on Debt Policy (DER) in Basic Material Sub-Sector Companies listed on the Indonesia Stock Exchange 2019-2023. While partially shows that there is a negative and significant influence of the Profitability variable on Debt Policy, while the liquidity and asset structure variables do not affect debt policy in Basic Material Sub-Sector Companies listed on the Indonesia Stock Exchange 2019-2023.